The influence of acute sprint interval training on the cognitive performance of male basketball players: An investigation of expertise-related differences - Manci, E.; Herold, F.; Günay, E.; Güdücü, Ç.; Müller, N. G.; Bediz, C. S. (International Journal of Environmental Research and Public Health, 2024)
Highly developed cognitive abilities are an important prerequisite for reaching elite athletic levels. This study aimed to investigate the effect of an acute sprint interval training (SIT) session on the cognitive performance of amateur and elite players. Eighteen amateur and ten elite male basketball players were included in this study. They were asked to perform an acute SIT consisting of the Wingate Test (i.e., four bouts of 30 s all-out sprints) on a cycle ergometer, interspersed with 4 min of active recovery. Before and after the acute SIT, three cognitive tests (i.e., Change Detection Test, Timewall Test, Mackworth Clock Test) were performed. Exercise-induced changes in cognitive performance and between-group differences were analyzed. We did not observe significant between-group differences in the performance of any cognitive test at the pretest, but elite basketball players outperformed the amateur players in specific measures of the Change Detection Test and Timewall Test after the acute SIT (p < 0.05). In addition, for the Clock Test, only the elite basketball players` performance improved from pre- to posttest. The current study`s findings suggest that male elite basketball players, compared to amateur basketball players, can preserve their cognitive performance after an acute bout of SIT.